Simulation on the effect of microtopography spatial variability on basin irrigation performance - Bai, Mei Jian, author; Xu, Di, author; Li, Yi Nong, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
Studying the impact of microtopography on irrigation performance is important for improving the management of basin irrigation systems. However, the limitation of field experiments will restrict the studies on the impact of microtopography spatial variability on basin irrigation performance. Thus, firstly this paper analyzed the spatial variability characteristics of field-measured Surface Relative Elevations (SRE). The correlations between the field geometry parameters and the spatial variability characteristics of SRE were evaluated, and the estimation methods for parameters of the semi-variogram of SRE were determined. Secondly, a microtopography stochastic generating model was built up based on the Monte-Carlo and the Kriging interpolation techniques. Lastly, the effect of spatial variability of microtopography on the performance of basin irrigation was evaluated by using of the numerical simulation model. Results showed that the microtopography undulation degree and the spatial distribution difference of undulation location had obvious effect on the basin irrigation performance. The average irrigation depth (Z'avg), corresponding to the water just cover the whole basin surface is increased while the irrigation application efficiency (Ea) and the irrigation uniformity (CU) is decreased when the field elevation non-uniformity, measured by the standard deviation of SRE (Sd) is increased. The effect of spatial distribution of undulation location on the irrigation performance was dependent upon the microtopography undulation degree, when Sd is less than 2cm the impacts can be neglected, while Sd is greater than 2cm, the influence should be considered.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.